Global burden of Alzheimer’s disease and other dementias (1990–2021): inequality, frontier, and decomposition analysis - Fu, Haishou; Huang, Huaqing; Liao, Shuzhen; Dai, Zhisen (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease and other dementias (ADOD) represent a growing global health crisis driven by the rapid aging of the population. Using data from the 2021 Global Burden of Disease (GBD) study, we provide updated global and national estimates of the ADOD burden from 1990 to 2021, quantify key risk factors, and offer evidence to guide resource allocation and prevention strategies.MethodsWe analyzed age-standardized incidence, prevalence, mortality, and disability-adjusted life years (DALYs) rates, along with the burden attributable to ADOD-related risk factors. Health disparities were assessed using the slope index of inequality and concentration index. We used frontier analysis to evaluate outcomes relative to development levels. Decomposition analysis identified the drivers of burden changes.ResultsGlobally, ADOD incidence, prevalence, and mortality increased significantly between 1990 and 2021 (156.54%, 160.81%, and 194.39%, respectively). High fasting blood glucose was the leading modifiable risk factor, contributing to 14.70% of global ADOD mortality, followed by elevated BMI and tobacco use. Burden trends varied across Socio-Demographic Index (SDI) regions, with high-middle SDI regions showing the highest prevalence. Gender-specific risk factor rankings showed high BMI as the second most significant factor in females, while tobacco use ranked second in males but declined over time. Decomposition analysis revealed the greatest increases in DALYs occurred in middle-SDI regions.DiscussionThis study reveals a considerable potential to reduce the ADOD burden in many countries. Although some metrics have stabilized or slowed in growth, significant inequalities remain, particularly in lower-SDI nations. Tailored strategies focusing on strengthening healthcare systems, targeting high-risk populations, and improving health education are essential to narrow these gaps. Greater international collaboration and open data sharing are also key to building a life-course management model for ADOD prevention and care, ultimately improving global health.